Impact of co-morbidity on mortality after oesophageal cancer surgery. Issue 9 (8th June 2015) - Backemar, L; Lagergren, P; Johar, A; Lagergren, J
Abstract: Background: There is limited knowledge of how co-morbidities influence survival after surgery for oesophageal cancer. This population-based cohort study investigated how Charlson co-morbidity index and specific co-morbidities influenced all-cause and disease-specific mortality. Methods: Data from all patients who underwent oesophageal cancer surgery in Sweden in 1987–2010, with follow-up until 2012, came from histopathology records, operation charts and nationwide registers. Associations between co-morbidities (Charlson co-morbidity index) and mortality were analysed using Cox proportional hazard regression with adjustment for potential confounding, and presented as hazard ratio (HR) with 95 per cent c.i. Results: Among 1822 patients there were 1474 deaths (80·9 per cent), of which 1139 (77·3 per cent) occurred between 91 days and 5 years after surgery. Overall all-cause mortality was increased in patients with a Charlson score of 2 or more (HR 1·24, 95 per cent c.i. 1·08 to 1·42), and those with a history of myocardial infarction (HR 1·23, 1·01 to 1·49) or congestive heart failure (HR 1·31, 1·04 to 1·67). Patients with squamous cell carcinoma had increased overall all-cause mortality if they had been diagnosed with cerebrovascular disease (HR 1·35, 1·00 to 1·83) or other cancers (HR 1·36, 1·09 to 1·71), whereas those with adenocarcinoma did not. A Charlson score of 1 or exposure to the co-morbidity groups peripheral vascular disease, chronic pulmonary disease, connective tissue disease, peptic ulcer disease, diabetes and liver disease did not increase mortality. The disease-specific results were generally similar to the all-cause mortality data. Conclusion: Co-morbidity with a Charlson score of 2 or more, previous myocardial infarction and congestive heart failure were associated with increased mortality after oesophageal cancer surgery undertaken with curative intent. Abstract : Cardiac co-morbidities count